How to Successfully Navigate Crisis-Driven Digital Transformations - Plattfaut, Ralf; Borghoff, Vincent (Management Information Systems Quarterly Executive, 2023)
The turmoil of the COVID-19 pandemic caused organizations to transform their operations on a massive scale, with many responding by increasing the use of digi- tal technologies and digitally transforming themselves. However, these crisis-driven digital transformations happened under new and unknown conditions. In this article, we identify crisis-related challenges to established digital transformation "logics" and describe how small and medium-sized organizations in Germany (the "German Mittel-stand") responded to these challenges. Based on their experiences, we provide recommendations for successfully navigating crisis-driven digital transformations.